Clinical cases of Gonorrhoeae - Islamov E.N.; Zhienbayev K.R.; Rysuly M.; Ospanova S.A.; Sukhanberdiyeva Z.M.; Idrissova A.S. (Research Retrieval and Academic Letters, 2024)
Gonorrhoeal infection occupies a leading position in the structure of STIs. Effective treatment of gonorrhoea and prevention of post-gonorrhoeal complications is the most important task of public health care. Ceftriaxone is the drug of choice in the treatment of uncomplicated gonorrhoea and currently shows high efficacy. Of particular concern is the emergence of antibiotic-resistant strains of gonorrhoea and, in particular, to ceftriaxone.